2022
DOI: 10.1371/journal.pone.0261652
|View full text |Cite
|
Sign up to set email alerts
|

Polish medical students facing the pandemic—Assessment of resilience, well-being and burnout in the COVID-19 era

Abstract: Introduction Recent reports indicate that COVID-19 pandemic has significant influence on medical professionals’ mental health. Strict limitations in clinical practice and social interactions within academic community, which had to be introduced, could lead to significant psychological distress in medical students. The aim of the study was to assess resilience, well-being and burnout among Polish medical students in the COVID-19 era. Methods The online survey consisting of validated questionnaires assessing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 43 publications
4
40
0
Order By: Relevance
“…Thirdly, the types of psychiatric diseases the cohort of psychiatrically ill students suffered from have not been examined. However, based on sociodemographic patterns of the participants, general epidemiological data [ 58 , 59 ], and reported mental health symptoms ( Table 1 ), it may be assumed that “psychiatrically ill” largely refers to depressive and anxiety disorders. The group, therefore, may not be very heterogeneous as it comprises socially active medical students, whose sociodemographic characteristics, health-related behaviors, and academic achievements are comparable to those of healthy students.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the types of psychiatric diseases the cohort of psychiatrically ill students suffered from have not been examined. However, based on sociodemographic patterns of the participants, general epidemiological data [ 58 , 59 ], and reported mental health symptoms ( Table 1 ), it may be assumed that “psychiatrically ill” largely refers to depressive and anxiety disorders. The group, therefore, may not be very heterogeneous as it comprises socially active medical students, whose sociodemographic characteristics, health-related behaviors, and academic achievements are comparable to those of healthy students.…”
Section: Discussionmentioning
confidence: 99%
“…Through a emotions, improve self-efficacy, and build up confidence and courage to cope with the crisis (81). Therefore, providing the necessary and proper social support services for medical students who experience high levels of burnout and low levels of resilience (82) during the online learning of the COVID-19 pandemic is crucial, as it might maximize the resilience level of medical students to some extent. For example, schools can offer online psychological counseling services or online courses on mental preparation for public health events for medical students (11).…”
Section: The Correlation Between Stress Social Support Resilience And...mentioning
confidence: 99%
“…Pharasi and Patra (83) concluded that resilience is a protective mechanism against burnout. Through the investigation of medical students, Forycka et al (82) reported that students with a higher level of resilience presented a better attitude toward online courses and showed lower levels of academic burnout.…”
Section: Resilience: Negatively Related To Academic Burnoutmentioning
confidence: 99%
“…According to S. Avijit and co-authors, the level of distress among students while studying using online technologies ranges from its absence (16.67%), mild (40%) to moderate (30.56%), and severe (12.78%) [41]. Students with a higher level of emotional stability demonstrated better attitudes toward online and hybrid classes [42]. Students' preference for online examinations is associated with academic specialization, efforts and time required for preparation, and correspondence of questions with educational material.…”
Section: Students' Academic Adaptation During the Pandemic Situationmentioning
confidence: 99%